Synthesis and characterization of Mn-doped CdSe quantum dots via inverse micelle technique / Nor Aliya Hamizi - Nor Aliya, Hamizi (2017)
Various sizes of manganese-doped cadmium selenide quantum dots (Mn-doped CdSe QDs) synthesized using inverse Micelle technique with organic solvent and surfactant possesses zinc blende structure with physical size ranging from 3 to 14 nm and crystallite size 2.46 to 5.46 nm respectively for 0 to 90 mins samples with narrow size distribution. Mn-doped CdSe QDs observed to growth larger QDs compared to pure CdSe QDs at significantly same reaction times. The lattice parameter compressed with QDs sizes growth due to the introduction of lattice strain due to the incorporation of Mn atoms into CdSe QDs lattice. The Mn-doped CdSe QDs shows a slight blue-shift on absorption and emission spectra’s compared to pure CdSe even though is possessed larger QDs. The band gap structure modification prominently affected by the lattice strain were transition of Stoke`s, Rayleigh to anti-Stoke`s shifts observed as the Mn doped CdSe QDs size growth. The typical red-shift of absorption and emission wavelength observed with growth of QDs sizes. The role of oleic acid acid as a surfactant and capping agent shows in FTIR spectra. The lattice strain tailored the binding energy between the ion prominently on the surface of the QDs with growth of QDs sizes.